Peculiar features of the low‐latitude and midlatitude ionospheric response to the St. Patrick's Day geomagnetic storm of 17 March 2015 - Nayak, Chinmaya (2016)
The current study aims at investigating and identifying the ionospheric effects of the geomagnetic storm that occurred during 17–19 March 2015. Incidentally, with SYM‐H hitting a minimum of −232 nT, this was the strongest storm of the current solar cycle 24. The study investigates how the storm has affected the equatorial, low‐latitude, and midlatitude ionosphere in the American and the European sectors using available ground‐based ionosonde and GPS TEC (total electron content) data. The possible effects of prompt electric field penetration is observed in both sectors during the main phase of the storm. In the American sector, the coexistence of both positive and negative ionospheric storm phases are observed at low latitudes and midlatitudes to high latitudes, respectively. The positive storm phase is mainly due to the prompt penetration electric fields. The negative storm phase in the midlatitude region is a combined effect of disturbance dynamo electric fields, the equatorward shift of the midlatitude density trough, and the equatorward compression of the plasmapause in combination with chemical compositional changes. Strong negative ionospheric storm phase is observed in both ionosonde and TEC observations during the recovery phase which also shows a strong hemispherical asymmetry. Additionally, the variation of equatorial ionization anomaly as seen through the SWARM constellation plasma measurements across different longitudes has been discussed. We, also, take a look at the performance of the IRI Real‐Time Assimilative Mapping during this storm as an ionospheric space weather tool.